Pengaruh Kualitas Kehidupan Kerja dan Keterampilan Kerja Terhadap Kinerja Karyawan di CV. Family Handicraft Tasikmalaya - Zainal Ruma (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of Quality of Work Life and Work Skills on Employee Performance (Census of Production Section Employees at CV. Family Handicraft Tasikmalaya). The method used is a quantitative approach with a sample of 50 respondents from the production employees of CV. Family Handicrafts. The data used are Primary Data and Secondary Data. The data analysis tool used is multiple linear regression analysis using SPSS version 25. The results show that simultaneously the Quality of Work Life and Work Skills have a significant effect on Employee Performance. Partially the Quality of Work Life has no significant effect on Employee Performance. Partially, work skills have a significant effect on employee performance.